Grid stabilization utilizing an AC/DC converter with adjustable power factor - Kustura, Ivan; Hanusa, Emin (My University, 2024)
Abstract This master thesis investigates the feasibility and consequences of implementing a modified single phase AC/DC converter with adjustable power factor, enabling a local phase compensation in the electrical grid. The theory was validated through simulations in LTspice and a real-world prototype was made from an existing evaluation kit from Texas Instruments. The desired power factor was obtained though a phase shift, employing two primary approaches: one analog and one digital. For the main analog case that provided the best signal integrity, a signal generator and a diode bridge were used to modify the phase angle. Conversely, the digital case utilized the Arduino UNO R4 with an integrated 12 bit digital to analog converter. The project showed that with an increased phase shift between the current and voltage, a greater local phase compensation could be achieved. This came at the expense of lower efficiency in the converter, transients through the zero crossings, and an increase in harmonics. For one case, where the output current was set to 0.5 A, the maximum amount of phase shift obtained was 13.5°. Simultaneously, the efficiency decreased from 94.3 % to 72.1 % and the total harmonic distortion of the current increased from 38.9 % to 72.6 %. Additionally, the prototype was tested in a microgrid environment with an AC side current of 1.59 A RMS, demonstrating its ability to achieve a local phase compensation. It was seen that when the current from the converter was high, 0.977 A RMS, the grid current could be adjusted significantly. Conversely, for a lower current, 0.111 A RMS, only minor adjustments could be made. Key regulations were also studied, including IEEE 519-2022 and IEC 61000 that govern performance and electromagnetic compatibility. Furthermore, the project investigated how local power factor adjustments via a single phase AC/DC converter could enhance grid efficiency and stability. This is of importance for voltage regulation with growing renewable energy integration. The technology could be implemented across Ericsson’s base stations, where each station could provide a local grid stabilization service.
Keywords: Keywords: AC/DC Converter, Power Factor Correction, Local Phase Compensation, Phase Shift, Grid Efficiency, Real-World Prototype.